SOSIALISASI PEMAHAMAN VIRGIN COCONUT OIL SEBAGAI MINYAK SEHAT DI DUSUN AIRLOUW, NEGERI URIMESSING, KECAMATAN NUSANIWE, KOTA AMBON - Grace Sipahelut, Sophia (HIRONO : Jurnal Pengabdian Masyarakat, 2025)
Virgin coconut oil (VCO) is the most famous coconut product because it has many health benefits, so it is dubbed the healthiest oil in the world. The purpose of this community service activity is to provide education to the community of Dusun Airlouw, Negeri Urimessing, Nusaniwe District, Ambon City about VCO and its health benefits and the process of making it. This community service activity involved 30 women. The methods used in this activity include socialization and evaluation. Based on the evaluation results, the socialization activities carried out had a significant impact on the community, where community knowledge about VCO as a healthy oil and its manufacturing process increased by over 90%. Participants were enthusiastic about being able to practice making VCO at home so that it could be consumed by their families.